2018
DOI: 10.1021/acs.est.7b06227
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Bioinspired Design for Constructing Membranes with Superhydrophobicity for Direct Contact Membrane Distillation

Abstract: Water flux and durability are the two critical parameters that are closely associated with the practical application of membrane distillation (MD). Herein, we report a facile approach to fabricate superhydrophobic polyimide nanofibrous membranes (PI NFMs) with hierarchical structures, interconnected pores, and high porosity, which was derived from the electrospinning, dual-bioinspired design, and fluorination processes. Bioinspired adhesive based on polydopamine /polyethylenimine (PDA/PEI) composite was first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(60 citation statements)
references
References 51 publications
1
59
0
Order By: Relevance
“…Thus, for an electrospinning deposition time of 10 min, the apparent contact angle value reached a value of 98.8 • and thus, was clearly not superhydrophobic. The use of longer electrospun PCL deposition times further increased the apparent water contact angle values, perhaps due to the presence of more fibrous structures, leading to enhanced roughness and a reduction in porosity [31] and showing values above 130 • . However, as explained above, only 120 min of PCL deposition generated the required morphology to achieve superhydrophobicity.…”
Section: Effect Of the Electrospun Pcl Deposition Time On Surface Wetmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, for an electrospinning deposition time of 10 min, the apparent contact angle value reached a value of 98.8 • and thus, was clearly not superhydrophobic. The use of longer electrospun PCL deposition times further increased the apparent water contact angle values, perhaps due to the presence of more fibrous structures, leading to enhanced roughness and a reduction in porosity [31] and showing values above 130 • . However, as explained above, only 120 min of PCL deposition generated the required morphology to achieve superhydrophobicity.…”
Section: Effect Of the Electrospun Pcl Deposition Time On Surface Wetmentioning
confidence: 99%
“…Additionally, PCL has an inherently low surface energy due to its chemical structure, so its hydrophobic fibers may also prevent water droplets from penetrating into the valleys between the ultrathin fibers and microparticles, which could help to further enhance the surface hydrophobicity [5,6]. In terms of previous works that have described hydrophobic surfaces prepared by EHDP with the additional incorporation of SiO 2 particles, Zhu et al [31] reported an apparent water contact angle of 152 • for a membrane consisting of SiO 2 nanoparticles bonded to an electrospun polyimide (PI) membrane by electrostatic attraction. Similarly, Su et al [16] successfully created highly porous membranes with superhydrophobic structures via simultaneous electrospraying of SiO 2 /dimethylacetamide (DMAc) colloids and electrospinning of poly(vinylidene fluoride) (PVDF)/DMAc solutions, which exhibited a water contact angle of 163 • .…”
Section: Minmentioning
confidence: 99%
“…In comparison to organic nanoparticles, SiO 2 nanoparticles have some unique advantages including good thermal stability, tunable particle size, good corrosion resistance, etc . Therefore, incorporating hydrophobic SiO 2 nanoparticles into electrospun nanofibers has become a common route to construct stable hydrophobic layer for nanofibrous membranes .…”
Section: Dopant Modified Electrospun Wandb Membranesmentioning
confidence: 99%
“…26,27 Electrospinning, a facile and powerful technique, provides a straightforward and inexpensive fabrication strategy for organic, inorganic or composite ber preparation. [28][29][30][31] The electrospun products have features such as a three-dimensional open porous structure, high surface area and huge aspect ratio, which would be benecial to mass transfer for effective wastewater treatment. However, it is still challenging to construct hierarchical porous carbon bers with an ultrahigh SSA for effective wastewater treatment.…”
Section: -12mentioning
confidence: 99%